Segmented filamentous bacteria in a defined bacterial cocktail induce intestinal inflammation in SCID mice reconstituted with CD45RBhigh CD4+ T cells - Štěpánková, Renata; Powrie, Fiona; Kofroňová, Olga; Hudcovic, Tomáš; Kozáková, Hana; Hrnčíř, Tomáš; Uhlig, Holm; Read, Simon; Řeháková, Zuzana; Benada, Oldřich; Heczko, Ploter; Strus, Magda; et al. (Inflammatory bowel diseases, 2007)
BACKGROUND: The aim was to analyze the influence of intestinal microbiota on the development of intestinal inflammation. We used the model of chronic inflammation that develops spontaneously in the colon of conventional severe combined immunodeficiency (SCID) mice restored with the CD45 RB(high) subset of CD4+T cells isolated from the spleen of normal BALB/c mice. METHODS: A CD4+CD45RB(high) subpopulation of T cells was purified from the spleen of conventional BALB/c mice by magnetic separation (MACS) and transferred into immunodeficient SCID mice. Germ-free (GF) SCID mice or SCID mice monoassociated with Enterococcus faecalis, SFB (segmented filamentous bacteria), Fusobacterium mortiferum, Bacteroides distasonis, and in combination Fusobacterium mortiferum + SFB or Bacteroides distasonis + SFB were used as recipients. SCID mice were colonized by a defined cocktail of specific pathogen-free (SPF) bacteria. Mice were evaluated 8-12 weeks after the cell transfer for clinical and morphological signs of inflammatory bowel disease (IBD). RESULTS: After the transfer of the CD4+CD45RB(high) T-cell subpopulation to SCID mice severe colitis was present in conventional animals and in mice colonized with a cocktail of SPF microflora plus SFB. Altered intestinal barrier in the terminal ileum of mice with severe colitis was documented by immunohistology using antibodies to ZO-1 (zona occludens). CONCLUSIONS: Only SFB bacteria together with a defined SPF mixture were effective in triggering intestinal inflammation in the model of IBD in reconstituted SCID mice, while no colitis was detected in GF mice or in mice colonized either with SPF microflora or monoassociated only with SFB or colonized by Bacteroides distasonis + SFB or Fusobacterium mortiferum + SFB.
Keywords: financování organizované; Animals; Intestinal Mucosa; myši SCID; průtoková cytometrie; slezina; kolitida; Microscopy, Electron, Scanning; mikroskopie elektronová rastrovací; převzatá imunita; Mice; Flow Cytometry; Adoptive Transfer; hyperplazie; Mice, Inbred BALB C; Mice, SCID; myši; Financing, Organized; modely nemocí na zvířatech; hypertrofie; myši inbrední BALB C; Leukocyte Common Antigens; Colitis; Spleen; Disease Models, Animal; hybridizace in situ fluorescenční; CD4-Positive T-Lymphocytes; zvířata; Hypertrophy; In Situ Hybridization, Fluorescence; Hyperplasia; antigeny CD45; střevní sliznice; CD4-pozitivní T-lymfocyty